Cardioprotective effect of isorhamnetin against myocardial ischemia reperfusion (I/R) injury in isolated rat heart through attenuation of apoptosis. Issue 11 (19th April 2020) - Xu, Yan; Tang, Chun; Tan, Shengyu; Duan, Juan; Tian, Hongmei; Yang, Yu
Abstract: In this study, we investigated the effects of isorhamnetin on myocardial ischaemia reperfusion (I/R) injury in Langendorff‐perfused rat hearts. Isorhamnetin treatment (5, 10 and 20 μg/mL) significantly alleviated cardiac morphological injury, reduced myocardial infarct size, decreased the levels of marker enzymes (LDH and CK) and improved the haemodynamic parameters, reflected by the elevated levels of the left ventricular developed pressure (LVDP), coronary flow (CF) and the maximum up/down velocity of left ventricular pressure (+dp/dtmax ). Moreover, isorhamnetin reperfusion inhibited apoptosis of cardiomyocytes in the rats subjected to cardiac I/R in a dose‐dependent manner concomitant with decreased protein expression of Bax and cleaved‐caspase‐3, as well as increased protein expression of Bcl‐2. In addition, I/R‐induced oxidative stress was manifestly mitigated by isorhamnetin treatment, as showed by the decreased malondialdehyde (MDA) level and increased antioxidant enzymes activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH‐Px). These results indicated that isorhamnetin exerts a protective effect against I/R‐induced myocardial injury through the attenuation of apoptosis and oxidative stress.